اللغة العربية والتعليم الجامعي - عوض سامي (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يتناول البحث مكانة اللغة العربية وسعتها، وثباتها، وفخر القرآن الكريم بأنه لسان عربي مبين، وأنه البلاغ المبين، فنحن نجد في العربية لغة عريقة، متينة التكوين، وافية الأصول، تميزت بالفصاحة والبيان فاستوعبت هداية القرآن الكريم، وحكمته الإنسانية، وما فيها من دلالات حضارية ويعرض البحث دور علمائنا في خدمة العربية حتى استطاعت هذه اللغة المباركة أن تستوعب ما نقل، وما ترجم، وتمكنت أن تضطلع بعبء المصطلحات العلمية، والفنية، وأثبتت قدرتها على استحداث المصطلح العلمي للعلوم المعروفة آنئذٍ، وثبتت أنها لغة علم، وتأليف، وتدريس. ويذكر البحث بإيجاز جهود روادنا المخلصين في تعريب العلوم، تلك الجهود التي طغى فيها الحافز الوطني على الرسالة العلمية التربوية، حتى ظاهر الحس الوطني الواجب العلمي فتكاملا كالمعجزة. ويعرض البحث قضيتين جديرتين بالدراسة: القضية الأولى: عدم الإلمام الكافي، أو التحصيل الجيد للغة العربية عند الطالب الجامعي غير المختص. القضية الثانية: شكوى معظم طلاب قسم اللغة العربية من صعوبة مقرر النحو والصرف. ويتبين البحث في خاتمته أن لغتنا العربية من أوسع اللغات قابلية للنمو والاشتقاق، ودلت على حيوية وافرة، وإمكانات في الغنى والتطور، وثبتت بوصفها لغة الحضارة الإنسانية سادت الفكر العالمي عدة قرون وإن الحفاظ على اللغة العربية وسلامتها هو حفاظ على الأمة ووحدتها، وإن نشرها في العالم اعتراف بأمة العرب ودورها في الحضارة الحديثة. The study deals with the importance of the Arbic language and its status,the uniqueness of the Koran as a great religious and literary text .We find in Arabic a long established, sophisticated language,distinguished by its eloquence, so that it accommodated the teaching of the Koran, its wisdom and cultural significance. The study shows the role our scientists play in serving the Arabic language to accommodate what was transferred or translated into it, including scientific or artistic terms. The Arabic language was able to modernize scientific terms and to prove its suitability for science, composition and teaching. The study briefly refers to the efforts pioneers have made in Arabizing sciences out of their non-nationalistic concern. The study tackles two problems. The first is the low level of the non-specialist students in the Arabic language. The second is the complaint of the students of Arabic literature regarding the difficulty they face in studying syntax and morophology. The conclusion stresses the strength of Arabic and its flexibility, its richness and its being the language of acivilization that had once influenced international thought .Therefore, preserving this language safeguards the nation, and spreading it worldwide is an acknowledgement of the role of Arabic in the modern civilization.